2021
DOI: 10.48550/arxiv.2111.13205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fractionalized holes in one-dimensional $\mathbb{Z}_2$ gauge theory coupled to fermion matter -- deconfined dynamics and emergent integrability

Abstract: We investigate the interplay of quantum one-dimensional discrete Z2 gauge fields and fermion matter with emphasis on fractionalized fermionic hole excitations whose deconfined nature we elucidate. In the limit of strong string tension, we uncover emergent integrable correlated hopping dynamics of holes which is complementary to the constrained XXZ description in terms of bosonic dimers. We analyze numerically quantum dynamics of spreading of an isolated hole and provide analytical understanding of its salient … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Previous theoretical studies of the system we consider focused on liquid phases at generic fillings and without the NN repulsion [25], near-full filling [26], and it has been shown that the NN repulsion leads to mesonic Mott insulating states at two-thirds filling [27]. At this commensurate filling, n = 2/3, the gauge-mediated confining potential and the NN repulsion act in concert without creating frustration, which results in a phase diagram with three different regimes: deconfined partons in the absence of the confining field, dimers (mesons) consisting of pairs of confined partons [25], and a Mott state of crystallized dimers [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies of the system we consider focused on liquid phases at generic fillings and without the NN repulsion [25], near-full filling [26], and it has been shown that the NN repulsion leads to mesonic Mott insulating states at two-thirds filling [27]. At this commensurate filling, n = 2/3, the gauge-mediated confining potential and the NN repulsion act in concert without creating frustration, which results in a phase diagram with three different regimes: deconfined partons in the absence of the confining field, dimers (mesons) consisting of pairs of confined partons [25], and a Mott state of crystallized dimers [27].…”
Section: Introductionmentioning
confidence: 99%